2016
DOI: 10.1007/s10071-016-1030-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of egg incubation temperature on the personality of oviparous reptiles

Abstract: Personality traits, defined as differences in the behavior of individual animals of the same species that are consistent over time and context, such as ‘boldness,’ have been shown to be both heritable and be influenced by external factors, such as predation pressure. Currently, we know very little about the role that early environmental factors have upon personality. Thus, we investigated the impact of incubation temperature upon the boldness on an oviparous reptile, the bearded dragon (Pogona vitticeps). Eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 42 publications
0
39
0
2
Order By: Relevance
“…Our results revealed an effect of the social, but not the predator rearing experience on neophobia. The willingness of an individual to take risks when exposed to novelty has been investigated in a wide range of taxa including fish (e.g., Frost, Winrow‐Giffen, Ashley, & Sneddon, ), amphibians (e.g., Caelson & Langkilde, ), reptiles (Carter et al., ; Siviter et al., ), birds (reviewed in Cockrem, ), and mammals (e.g., Carter, Marshall, Heinsohn, & Cowlishaw, ) and has important implications for fitness in the context of foraging, reproductive success and predation (e.g., Biro & Stamps, ). The ability to survive predator encounters is one of the strongest selective forces (Lima & Dill, ; Peacor & Werner, ) and it has been shown that neophobia has an important role in predator avoidance (e.g., Carter et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed an effect of the social, but not the predator rearing experience on neophobia. The willingness of an individual to take risks when exposed to novelty has been investigated in a wide range of taxa including fish (e.g., Frost, Winrow‐Giffen, Ashley, & Sneddon, ), amphibians (e.g., Caelson & Langkilde, ), reptiles (Carter et al., ; Siviter et al., ), birds (reviewed in Cockrem, ), and mammals (e.g., Carter, Marshall, Heinsohn, & Cowlishaw, ) and has important implications for fitness in the context of foraging, reproductive success and predation (e.g., Biro & Stamps, ). The ability to survive predator encounters is one of the strongest selective forces (Lima & Dill, ; Peacor & Werner, ) and it has been shown that neophobia has an important role in predator avoidance (e.g., Carter et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Illustrating potential effects of climate change on animal cognition, our final two studies are examples of research on the effects of changing temperature in reptiles and amphibians, taxonomic groups that have received only minimal attention in this regard. Whereas Siviter et al (2016) focus on the effects of incubation temperature on reptile personality, Amiel et al (2016) suggest that increased incubation temperatures may directly modify brain structures and related learning abilities in scincid lizards (Bassiana duperreyi). These studies highlight the need to design long-term studies in which temperature is gradually stepped up across generations in levels that mimic predicted temperature rises.…”
Section: Introductionmentioning
confidence: 99%
“…First, other avian parental effects, such as hormone deposition to the egg, influence behavioral traits in birds (Daisley, Bromundt, Möstl, & Kotrschal, 2005;Forstmeier, Coltman, & Birkhead, 2004). Second, incubation temperature is known to influence boldness and fear-related behaviors in nonavian reptiles (Siviter et al, 2017;Trnik, Albrechtová, & Kratochvíl, 2011), and we suspect a similar effect exists for birds. Third, incubation temperature influences avian corticosterone levels (DuRant et al, 2010;Wada et al, 2015), growth rates (DuRant et al, 2010), and metabolic rates (DuRant et al, 2012b;Nord & Nilsson, 2011), all of which are related to proactive/reactive behavioral traits in other species (Biro & Stamps, 2010;Careau et al, 2008;Carere, Groothuis, Möstl, Daan, & Koolhaas, 2003;Cockrem, 2007;Stamps, 2007;Stöwe, Rosivall, Drent, & Möstl, 2010).…”
Section: Introductionmentioning
confidence: 89%